Effect of slaked lime and aluminum sulfate on the properties of dry-mixed masonry mortar. (20th August 2018) - Wang, Yuli; He, Hang; He, Fengxia
Highlights: The optimal ratio of slaked lime and aluminum sulfate was determined. The compound admixture can better improve the performances of mortar. The compound admixture promotes the formation of AFt. Results provide new insights into potential ways to improve the performances of mortar. Abstract: There are some drawbacks, such as bleeding, poor cohesiveness, etc, because the water to cement (W/C) ratio of dry-mixed masonry mortar is greater. Therefore, the influences of the slaked lime and aluminum sulfate on performances of masonry mortar were studied. The results show that the optimum ratio of slaked lime to aluminum sulfate by weight is 5–1, and the consistency, bleeding and strength of the mortar can be better improved by the two compounds. The consistency increases by 12.3%, the bleeding water decreases by 6.1% and 28d compressive strength of mortar increases by 27.3% when the content of compound admixture is 6 wt%. The results of SEM, XRD and TG-DTA show that the amount of AFt and C-S-H is changed by the slaked lime and aluminum sulfate, the hydration products and hardened structures are optimized by the compound admixture, and the performances of mortar are improved. This is a good reference value for the performance improvement of masonry mortar.